2014
DOI: 10.1590/0074-0276130519
|View full text |Cite
|
Sign up to set email alerts
|

Large indoor cage study of the suppression of stable Aedes aegypti populations by the release of thiotepa-sterilised males

Abstract: The sterile insect technique (SIT) is a promising pest control method in terms of efficacy and environmental compatibility. In this study, we determined the efficacy of thiotepa-sterilised males in reducing the target Aedes aegypti populations. Treated male pupae were released weekly into large laboratory cages at a constant ratio of either 5:1 or 2:1 sterile-to-fertile males. A two-to-one release ratio reduced the hatch rate of eggs laid in the cage by approximately a third and reduced the adult catch rate by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…These methods aim either at replacing a target population with a strain having reduced vector competence or at suppressing an Ae. aegypti natural population below the threshold required for disease transmission (Hoffmann et al, 2011; Bourtzis et al, 2014, 2016; Carvalho et al, 2014; Gato et al, 2014; Lees et al, 2015). Both the replacement and the suppression methods have pros and cons (for a brief review see Bourtzis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These methods aim either at replacing a target population with a strain having reduced vector competence or at suppressing an Ae. aegypti natural population below the threshold required for disease transmission (Hoffmann et al, 2011; Bourtzis et al, 2014, 2016; Carvalho et al, 2014; Gato et al, 2014; Lees et al, 2015). Both the replacement and the suppression methods have pros and cons (for a brief review see Bourtzis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a previous study performed in our lab showed that the weekly release of chemosterilized males at a 5:1 ratio with the fertile males was sufficient to eliminate a caged population of Ae. aegypti within 15 weeks [18]. Certainly, the trials of SIT suppression of mosquito-caged populations should be interpreted carefully, but gives gross evidences of the efficacy of the technique, as part of the progressive, stepwise evaluation of sterile mosquitoes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Progressive assessment of SIT from laboratory to large cages performed prior to the present study is valuable because it allows for systematic assessment of possible effects on mosquito survival and performance under conditions increasingly more natural [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…[9c,29] Recently in the face of impinging threats from Dengue, Chikungunga and Zika virus, mass release of aziridine-sterilized males has been revived as a part of an integrated program for control of Aedes vectors in Cuba. [30] …”
Section: Toxicology Of Aziridine-phosphoryl Chemosterilantsmentioning
confidence: 99%